A new European species of Pegomya Robineau-Desvoidy (Diptera: Anthomyiidae) near P. testacea (De Geer) - Michelsen, Verner (Zootaxa, 2006)
A new species of Pegomya Robineau-Desvoidy, P. prisca sp. nov., is described from Europe (Sweden, Czech Republic and Slovakia). It belongs to a species group together with the widespread West Palaearctic P. testacea (De Geer) and P. hamata Wei described from China. Differential descriptions and illustrations of the terminalia are given for the two species of the Pegomya testacea species group found in Europe. Morphological and other evidence suggests that saprophagous larval habits persist in a few species of Pegomya represented by the P. testacea and P. ruficeps species groups.